Magamp Regulated Isolated AC-DC Converter with High Power Factor - Volodymyr Yaskiv; Alexander Abramovitz; Keyue Smedley; Anna Yaskiv (Communications - Scientific letters of the University of Zilina, 2015)
This paper evaluates the performance of magnetic amplifier regulator in isolated off-line power supplies with power factor correction stage. A research of operation modes of power converter, based on high frequency magnetic amplifiers, with power factor correction was conducted for the first time. Simplified controller circuitry is suggested and analyzed. Experimental results are reported.